Genetic diversity assessment and estimation of phylogenetic relationships among 26 Fagaceae species using ISSRs - Coutinho, João Paulo; Carvalho, Ana; Lima-Brito, José (Biochemical Systematics and Ecology, 2014)
The family Fagaceae includes several species and presents huge genetic variability. In the last two decades, several genetic studies about phylogenetics and genetic diversity of Fagaceae have emerged. ISSR markers were used to evaluate the genetic diversity of 26 species of Fagaceae belonging to the genera Castanea, Fagus and Quercus. Among several primers tested, 17 were selected for the evaluation of diversity and estimation of genetic relationships. A total of 371 ISSR markers were produced and each primer revealed high polymorphism. Specific ISSR markers for the Quercus infrageneric groups were amplified. ISSRs proved to be a reliable tool for the discrimination of the analyzed species per genus, infrageneric group and/or ecological origin.
Keywords: Fagaceae; Genetic variability; Inter-simple sequence repeats (ISSRs); Quercus